Efek Interaksi Sulfate (SO42-) dan Kromium (CrO42-) terhadap Pertumbuhan dan Akumulasi Cr6+ pada Tagetes erecta L. - Sri Kasmiyati; Gabriella L. Mataradja (Agric, 2023)
Chromium is a heavy metal that is toxic, bioaccumulative, persistent, and cannot be decomposed in the environment. The Cr6+ ion is a chromium ion that has the highest toxicity among other chromium ions, so its presence in the environment is hazardous for plants, animals, and humans. Sulfur is an essential element for plants, whose presence can reduce Cr6+ concentrations in the terrestrial environment by inhibiting the uptake of Cr6+ by plants. Tagetes erecta is a bioremediation agent plant that can remediate land polluted with Cr6+ waste. In this research, we studied the growth of T. erecta in media polluted with Cr6+ and sulfate and its ability to accumulate of Cr6+. Several parameters observe in this experiment, i.e. growth parameters, namely plant height, number of leaves, number of flowers measured at the end of the study, dry weight, root length, and Cr6+ concentration estimated using the diphenylcarbasid method. The results showed that the plant height of T. erecta. was not significantly different, and sulfate addition did not affect plant height. The addition of sulfate affected the number of leaves and flowers, dry weight of root shoots, root length, and Cr6+ content in T. erecta. polluted with Cr6+. so that in these parameters, there was a significant difference in the addition of Cr6+ and sulfate on growth of T. erecta and its ability to Cr accumulation.